HEGEMONY IN UNTOUCHABLE BY MULK RAJ ANAND - Lovenna Theresia Parapat; Anselmus Chartino Ade (LPPM Universitas Katolik Santo Thomas Medan, 2025)
This study aims to analyze the social hierarchy and marginalization in Mulk Raj Anand's Untouchable through the theory of Cultural Marxism, especially Antonio Gramsci's concept of hegemony. This study uses a qualitative narrative method with a descriptive approach. The method used is descriptive qualitative. Data collection was conducted through several steps, namely reading and understanding the novel thoroughly, noting relevant quotations, collecting supporting theoretical references, and classifying the data into categories. Data analysis used the Miles and Huberman framework, which includes data reduction, data display, and conclusion drawing. The results of the study show that the social hierarchy in the novel is reflected through the caste system that places the main character, Bakha, as an